VD_FINDINFO AP / 2011 / 55 vom 9. Dezember 2010 - VD Tribunal cantonal (2010)
PORNOGRAPHIE, ADMISSION PARTIELLE, PEINE PÉCUNIAIRE, FIXATION DE LA PEINE | 197 ch. 3 CP, 44 al. 1 CP, 47 CP, 157 al. 1 CPP